2012
DOI: 10.1007/s10802-012-9637-4
|View full text |Cite
|
Sign up to set email alerts
|

Anger and Irritability Symptoms among Youth with ODD: Cross-Informant Versus Source-Exclusive Syndromes

Abstract: We examined differences in co-occurring psychological symptoms and background characteristics among clinically referred youth with oppositional defiant disorder (ODD) with and without anger/irritability symptoms (AIS) according to either parent or teacher (source-exclusive) and both informants (cross-informant), youth with noncompliant symptoms (NS) of ODD, and non-ODD clinic controls. Parents and teachers evaluated 1127 youth (ages 6–18) with a DSM-IV-referenced rating scale to assess ODD and co-occurring psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 59 publications
5
37
1
Order By: Relevance
“…Furthermore, sensitivity of the clinical cutoff point for Behavior Regulation appeared to be somewhat better in the younger age group (3.5-4.5 years) than in the older age group (4.5-5.5 years), maybe because older preschoolers can better inhibit their own behavior than younger preschoolers. The better results for referred patients with clinical scores on the TRF 1.5-5 (T score above 70) are in line with evidence that youth with symptoms according to both parent and teacher had more mental health concerns than youth with symptoms according to either parent or teacher (Gadow & Drabick, 2012).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, sensitivity of the clinical cutoff point for Behavior Regulation appeared to be somewhat better in the younger age group (3.5-4.5 years) than in the older age group (4.5-5.5 years), maybe because older preschoolers can better inhibit their own behavior than younger preschoolers. The better results for referred patients with clinical scores on the TRF 1.5-5 (T score above 70) are in line with evidence that youth with symptoms according to both parent and teacher had more mental health concerns than youth with symptoms according to either parent or teacher (Gadow & Drabick, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Based on ROC curve analyses the sensitivity and specificity for the ADHD diagnosis when compared with DBD diagnoses appeared to be better for ADHD than for DBD. This may be due to the cross-situational character of ADHD symptoms (Gadow & Drabick, 2012). In contrast, ODD symptoms may be present in just one context (at home or at school).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of full or partial scalar invariance supports the concept of ODD as a source-specific disorder, which is also the view of other authors (Drabick, et al, 2007;Gadow & Drabick, 2012;Strickland, Hopkins, & Keenan, 2012), and highlights the need of including both reporters (parent and teachers) in the assessment process of children with ODD. Further research may confirm whether scalar equivalence is maintained or not in older individuals.…”
Section: Discussionsupporting
confidence: 73%
“…This reformulation has occurred in the context of several studies, which found distinct affective dimensions within ODD (35)(36)(37)(38)(39). ODD has reorganized within the DSM-V to emphasize this finding.…”
Section: The Centrality Of Affect and Er In Common Adolescent Presentmentioning
confidence: 99%